2018
DOI: 10.1080/21691401.2018.1482306
|View full text |Cite
|
Sign up to set email alerts
|

Combined immunization against TGF-β1 enhances HPV16 E7-specific vaccine-elicited antitumour immunity in mice with grafted TC-1 tumours

Abstract: Therapeutic vaccine appears to be a potential approach for the treatment of human papillomavirus (HPV)-associated tumours, but its efficacy can be dampened by immunosuppressive factors such as transforming growth factor (TGF)-β1. We sought to investigate whether active immunity against TGF-β1 enhances the anti-tumour immunity elicited by an HPV16 E7-specific vaccine that we developed previously. In this study, virus-like particles of hepatitis B virus core antigen were used as vaccine carriers to deliver eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
5
1
Order By: Relevance
“…Neither the neutralization of IL-10 or TGF-β nor the inhibition of arginase resulted in the enhancement of our combined IT. These observations differ from studies conducted in tumors induced with parental TC-1 cells, as targeting either IL-10 or TGF-β enhanced the therapeutic effect of various immunotherapies or increased infiltration with an anti-tumor cell population in these tumors [ 61 , 62 , 63 ]. This difference can be caused by the higher resistance of tumors with MHC-I downregulation to IT and the different mechanisms of tumor cell killing.…”
Section: Discussioncontrasting
confidence: 72%
“…Neither the neutralization of IL-10 or TGF-β nor the inhibition of arginase resulted in the enhancement of our combined IT. These observations differ from studies conducted in tumors induced with parental TC-1 cells, as targeting either IL-10 or TGF-β enhanced the therapeutic effect of various immunotherapies or increased infiltration with an anti-tumor cell population in these tumors [ 61 , 62 , 63 ]. This difference can be caused by the higher resistance of tumors with MHC-I downregulation to IT and the different mechanisms of tumor cell killing.…”
Section: Discussioncontrasting
confidence: 72%
“…46 In this study, potential linear B cell epitopes of mouse FGF-2 were screened by synthesizing a set of overlapping peptides covering the whole sequence of FGF-2 molecules. Theoretically, a peptide with 5-6 amino acids can constitute the smallest B cell epitope; 47 however, according to our previous experiences, 48,49 a peptide with a length of 11-15 amino acids holds a great chance to elicit a high titer of antibodies with a high affinity. In this study, we designed and synthesized peptides with a length between 18 and 29 aa and obtained a set of 13 peptides with a peptide overlapping two adjacent peptides to avoid missing any possible linear epitopes at the joint.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that TGF-β1- and HPV E7-presented chimeric virus-like particles significantly suppressed tumor growth through TME regulation. 20 , 33 SQSTM1/p62 also participates in regulating the TME via TAMs, which promote tumor growth. Endogenous and exogenous stimuli induce mitochondrial damage in TAMs that results in the production of mitochondrial DNA (mtDNA) and reactive oxygen species (ROS), which directly activate NLRP3 inflammasome-mediated pyroptosis along with production of the tumor-promoting cytokines IL-1β and IL-18.…”
Section: Discussionmentioning
confidence: 99%
“…model, 1 × 10 6 cells were inoculated into the second breast fat pad. The mice were monitored three times per week for tumor growth using a slide caliper as described previously, 20 and the mice were sacrificed at experiment endpoints. To generate a murine lung metastasis model, mice were intravenously ( i.v. )…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation